Investigation of tribological properties of CuO/palm oil nanolubricant using pin-on-disc tribotester. Issue 1 (14th February 2018) - Azman, Nurul Farhanah; Samion, Syahrullail; Sot, Mohamad Nor Hakim Mat
Abstract : It has been proposed that nanoparticles have the ability to enhance the tribological properties of lubricants. In the present research, the tribological properties of a palm-oil-based nanolubricant with copper (II) oxide (CuO) nanoparticles have been investigated experimentally using a pin-on-disc tribotester. The experiments were conducted at a sliding speed of 0·2 m/s and an applied load of 9·8 N, which corresponds to a contact pressure of 0·93 GPa for 60 min duration. Commercial mineral oil (SAE40) was used for comparison purposes. The results show that the tribological properties of the palm-oil-based lubricant were improved with the presence of copper (II) oxide nanoparticles, showing huge reductions in coefficient of friction and wear scar diameter of about 56 and 48%, respectively. The findings revealed that the presence of copper (II) oxide in palm kernel oil (PKO) reduced the roughness of the pin surface by 43·7%. The results also show that the tribological properties of the copper (II) oxide/palm-oil-based nanolubricant were comparable to those of SAE40.